OPTIMIZING LARGE-SCALE DATA LOADING THROUGH TABLE PARTITIONING - Venkata Prasanna Kumar Pentakota, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Humana's successful implementation of optimized data loading processes through table partitioning and parallel execution strategies showcases a transformative approach to healthcare data infrastructure. The organization addressed critical challenges in data processing, system performance, and resource utilization through comprehensive analysis, strategic architectural design, and phased deployment. The implementation delivered significant improvements across operational efficiency, business impact, and technical capabilities, demonstrating how modern healthcare organizations can effectively manage large-scale data processing while maintaining compliance with industry regulations and ensuring high availability of critical healthcare services.